2020
DOI: 10.1186/s12891-020-03207-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel anterior curved incision combined with MIPO for Pilon fracture treatment

Abstract: Backgrounds: Poor prognosis was reported for complex Pilon fractures involving severe soft tissue damage. It is therefore useful to explore the evolution of different treatment strategies in an effort to reconstruct the axial alignment and articular surface, while minimizing additional damage to the surrounding soft tissues. Methods: Seventeen patients with Pilon fractures were enrolled in this retrospective study from December 2009 to October 2014. The injuries were graded according to AO Classification and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 17 publications
3
18
0
1
Order By: Relevance
“…The restoration of ankle movement may introduce physiological loading that is bene cial to the healing and grinding of the articular surface, and reduce the risk of developing posttraumatic osteoarthritis. [21] Although we have demonstrated satisfactory outcomes in this study, the use of the described technique for tibiotalar joint reconstruction should be considered with caution. It has been reported that complete reduction in pilon fractures can lead to complete failure, such as non-union, avascular necrosis and osteomyelitis.…”
Section: Discussionmentioning
confidence: 62%
“…The restoration of ankle movement may introduce physiological loading that is bene cial to the healing and grinding of the articular surface, and reduce the risk of developing posttraumatic osteoarthritis. [21] Although we have demonstrated satisfactory outcomes in this study, the use of the described technique for tibiotalar joint reconstruction should be considered with caution. It has been reported that complete reduction in pilon fractures can lead to complete failure, such as non-union, avascular necrosis and osteomyelitis.…”
Section: Discussionmentioning
confidence: 62%
“…However, the characterization at 18 months in this study does not give definitive evidence of the repair tissue composition, and longer-term follow-up with noting of possible complications such as arthritic changes are necessary [24,25]. Nevertheless, the restoration of ankle movement may introduce physiological loading that is beneficial to the healing and grinding of the articular surface, and reduce the risk of developing post-traumatic osteoarthritis [26].…”
Section: Discussionmentioning
confidence: 87%
“…However, the characterization at 18 months in this study does not give de nitive evidence of the repair tissue composition, and longer-term follow-up with noting of possible complications such as arthritic changes are necessary [24,25]. Nevertheless, the restoration of ankle movement may introduce physiological loading that is bene cial to the healing and grinding of the articular surface, and reduce the risk of developing post-traumatic osteoarthritis [26].…”
Section: Discussionmentioning
confidence: 89%